2021
DOI: 10.1155/2021/8936907
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum Exhibits Antioxidant and Cytoprotective Activities in Porcine Intestinal Epithelial Cells Exposed to Hydrogen Peroxide

Abstract: Probiotics are widely used for protection against stress-induced intestinal dysfunction. Oxidative stress plays a critical role in gastrointestinal disorders. It is established that probiotics alleviate oxidative stress; however, the mechanism of action has not been elucidated. We developed an in vitro intestinal porcine epithelial cells (IPEC-J2) model of oxidative stress to explore the antioxidant effect and potential mode of action of Lactobacillus plantarum ZLP001. The IPEC-J2 cells were preincubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 61 publications
2
15
2
Order By: Relevance
“…First, exopolysaccharides from L. plantarum reduced the production of pro-inflammatory cytokines (tumor necrosis factor-α, interferon-gamma, and interleukin (IL)-12) and enhanced the anti-inflammatory cytokine IL-10 [20]. In addition, L. plantarum is a promising probiotic bacterium that can potentially alleviate oxidative stress [21]. These results are consistent with our findings that FC levels, indicating MC, were significantly decreased in the L. plantarum group.…”
Section: Discussionsupporting
confidence: 89%
“…First, exopolysaccharides from L. plantarum reduced the production of pro-inflammatory cytokines (tumor necrosis factor-α, interferon-gamma, and interleukin (IL)-12) and enhanced the anti-inflammatory cytokine IL-10 [20]. In addition, L. plantarum is a promising probiotic bacterium that can potentially alleviate oxidative stress [21]. These results are consistent with our findings that FC levels, indicating MC, were significantly decreased in the L. plantarum group.…”
Section: Discussionsupporting
confidence: 89%
“…Here, E. coli and S. Typhimurium were used to induce oxidative stress in IPEC-J2 cells. The exact mechanism of how E. coli and Salmonella exert their oxidative stress-inducing effect is obscure, but pathogens may produce oxygen to generate an aerobic environment, thus establishing oxidative stress conditions in the intestines [ 8 ]. To confirm the antioxidant effect of the application of E. faecium as a pre-treatment, co-treatment, and post-treatment, we determined the capacity of the treatment methods for the alleviation of ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that E. faecium could alleviate the oxidative stress caused by E. coli and S. Typhimurium. Interestingly, certain probiotics have been shown to mitigate induced ROS production, and that pre-treatment of IPEC-J2 cells with L. plantarum ZLP001 reduced the ROS burst evoked by H 2 O 2 in IPEC-J2 cells [ 8 ], supporting the potential beneficial effect of probiotics on ROS generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has revealed that lactic acid bacteria effectively activate nuclear factor erythroid 2-related factor 2 (Nrf2) antioxidant response elements (AREs), which further initiate the expression of serial antioxidant genes and exert antioxidant and anti-inflammatory effects [ 5 7 ]. Lin et al reported that Lactobacillus plantarum AR501 , isolated from Chinese food, markedly elevated the expression levels of Nrf2 and several antioxidant genes, including the glutathione S-transferase GSTO1, haem oxygenase-1 (HO-1), glutamate cysteine ligase (GCL), and NAD(P)H: quinone oxidoreductase-l (NQO1), in mouse livers [ 8 ], indicating that Nrf2/HO-1 is an important antioxidant signalling pathway.…”
Section: Introductionmentioning
confidence: 99%